THE ROLE OF COVERT INVESTIGATIVE ACTIVITIES IN OFFICIAL MISCONDUCTS (Law and world, 2019)
The present article analyzes the necessity of applying covert investigative activities to all categories of ofﬁcial misconducts. It addresses to all types of covert investigative activities which are mostly used in the course of investigation of ofﬁcial misconducts. The article further discusses domestic and international legal tools and practices of using covert investigative activities. The author draws considerable attention to the applicable standards of covert investigative activities and suggests recommendations in this respect, which protect the interests of individuals and that of investigation. Although, application of covert investigative activities poses potential threat to human rights, on the other hand, the interest of an effective investigation of ofﬁcial misconducts is an essential element of crime prevention and the rule of law.